2016
DOI: 10.1002/ccd.26596
|View full text |Cite
|
Sign up to set email alerts
|

Preprocedural fractional flow reserve and microvascular resistance predict increased hyperaemic coronary flow after elective percutaneous coronary intervention

Abstract: PCI affected MR. Pre-PCI FFR and MR were independent predictors of post-PCI changes in hyperaemic coronary flow. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…In those lesions, hyperemic coronary flow might increase if the increased resistance is reduced after revascularization, as suggested by our recent studies 13, 30. The exact mechanism and pathophysiology of increased or decreased hyperemic microvascular resistance were not known and the change in microvascular resistance and its effect on absolute coronary flow after revascularization remain elusive.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In those lesions, hyperemic coronary flow might increase if the increased resistance is reduced after revascularization, as suggested by our recent studies 13, 30. The exact mechanism and pathophysiology of increased or decreased hyperemic microvascular resistance were not known and the change in microvascular resistance and its effect on absolute coronary flow after revascularization remain elusive.…”
Section: Discussionmentioning
confidence: 90%
“…It has been proposed that the presence of microvascular dysfunction is not an obstacle for making decisions based on FFR, provided that minimal and constant microvascular resistance with induced hyperemia is deemed to be nonreversible or consistent before and after revascularization 28, 29. However, several studies reported the evidence of serial changes in adenosine‐induced microvascular resistance before, after, and during follow‐up post‐PCI 13, 30, 31. van de Hoef et al also reported that identification of epicardial disease severity by FFR is partly obscured by microvascular resistance and that FFR increased with increasing hyperemic microvascular resistance to epicardial disease of equivalent severity 15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although one of the important goal of PCI is to increase coronary blood flow by targeting epicardial coronary stenosis, few studies have confirmed the relationship between pre‐PCI FFR value and post‐PCI increased coronary flow. Furthermore, an increase in coronary flow after PCI may not be determined solely by modification of the epicardial lesion by PCI . Therefore, we hypothesized that patients with lesions within the FFR grey zone were more likely not to experience increased hyperemic coronary flow evaluated by using coronary physiological indices after PCI, compared with those with low FFR values.…”
Section: Introductionmentioning
confidence: 99%
“…To test this hypothesis, we investigated the serial change in coronary flow reserve (CFR), index of microcirculatory resistance (IMR), and transit time (Tmn) after PCI and compared changes in these indices between grey‐zone FFR and low‐FFR territories. These physiological indices have been validated and used as surrogates of coronary flow profiles and IMR has been used to represent the status of microcirculation . The predictors for improvement of hyperemic coronary flow were also determined in each group to evaluate whether FFR values or other indices provide predictive efficacy.…”
Section: Introductionmentioning
confidence: 99%